ANALISIS PERLAKUAN AKUNTANSI ATAS SELISIH KURS DALAM TRANSAKSI PEMBELIAN MATA UANG ASING PADA LABA BERSIH PT. KARYA SUKSES KREASINDO DI SURABAYA - Nova Daniar Listari; Bachtiar Rahman Halik (Jurnal Ekonomi, Bisnis dan Social, 2024)
This research aims to determine changes in exchange rates that occur in foreign currency transactions which affect PT. Karya Sukses Kreasindo Surabaya. The final assignment is prepared using secondary data in the form of Financial Reports. PT Karya Sukses Kreasindo Surabaya in 2021. The analysis method is descriptive qualitative. Apart from that, the author also examines how the accounting treatment of exchange rate differences is carried out by PT. Karya Sukses Kreasindo Surabaya and compare it with Financial Accounting Standards (SAK). As a result of this research, the author wants to show how large or small the influence of exchange rate differences made by PT. Karya Sukses Kreasindo Surabaya and compare in accordance with Financial Accounting Standards (SAK). Exchange rates that fluctuate and are difficult to predict cause companies to experience losses or gains from exchange rate differences when carrying out foreign currency transactions, especially credit purchase transactions and incurring business debts. As a result, the exchange rate difference will have an impact on financial statements. PT. Karya Sukses Kreasindo Surabaya, especially the Profit/Loss Report and Balance Sheet.